The Heart at the Heart of the World: Ecospirituality, Reparation, and the Sacred Heart - Frohlich, Mary (MELINTAS, 2024)
This essay explores a new way of thinking about the theology and spirituality of the Sacred Heart devotion. The essay begins by identifying the danger of global ecological collapse as a crisis that requires us to rethink traditional theologies. After reviewing the history of the Sacred Heart devotion and how it became associated with the theology of reparation, the essay proposes a renewed Christology that discovers the Heart of Jesus truly at the heart of the world—including at the heart of the Earth’s physicality and its ecological systems. In this view, the damage humans are inflicting on the whole community of Earth creatures literally pierces the Heart of Jesus. Our embrace of his Heart at the heart of the world will awaken us to a spirituality of reparation as compassionate accompaniment of the suffering Earth and its creatures.